Pelatihan Mind-Body Wellness dan Deteksi Dini Risiko Metabolik di Komunitas Pekerja Kelurahan Maleer, Bandung - Halomoan, Roni; Thesalonika, Lona; Sudrajat, Agus; Trimastuti, Wahyu; Gunawan, Ramdhan (PADMA, 2023)
Worker health contributes greatly to productivity and social welfare. High levels of work stress, lack of physical activity, and unhealthy eating habits can increase the risk of metabolic diseases such as hypertension, diabetes mellitus, and obesity. This Community Service Activity (PKM) aims to increase the knowledge and awareness of workers in Maleer Village, Bandung, about the importance of balancing physical and mental health (mind-body wellness) and conducting early detection of metabolic risks. The implementation methods included health education, relaxation technique training (mindfulness breathing and progressive muscle relaxation), and basic health checks (blood pressure, blood sugar levels, and body mass index). A total of 30 participants from the working community took part in this activity. The results showed a 45% increase in knowledge after the training, and 30% of participants were found to have mild to moderate metabolic risks. This activity demonstrates that mind-body wellness training is effective in increasing public awareness and skills in maintaining physical and mental health.